Ganguan Aspek Fonologi Pada Anak Penderita Disleksia Usia 8 Tahun - Ghea Putri Amelia (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study is to describe the forms of phonological disorders, especially the pronunciation of Indonesian sounds that occur in children aged 8 years with dyslexia and identify the factors that cause language disorders in phonological aspects in children aged 8 years with dyslexia. The data source of this study was a dyslexic patient named at SDN Karang Tengah 07 Tangerang Selatan with an age of 8 years. The data were analyzed using qualitative descriptive methods, because this study requires data in the form of written or oral descriptions of the research subjects. This method was chosen because it is based on facts or phenomena that occur to the speaker. The researcher uses psycholinguistic theory, the theory of language disorders (Dyslexia), and the form of disorders in phonological aspects in this study. The results of this study can be concluded that children with dyslexia experience phonological aspects of the pronunciation of Indonesian sounds, namely consonant and vocal sounds. These disturbances occur in two types, namely substitution, addition, left-right reversal (inversion), deletion. Dyslexia in this study was caused by an accident from an early age, so that the nerves of the brain were disrupted and caused delays in language skills, one of which was reading so that they experienced disturbances in the phonological aspect.